Executive Financial Literacy and Corporate Performance: Evidence from Small and Medium‐Sized Enterprises in China. (16th January 2023) - Tian, Guangning; Zhou, Shuyuan; Qi, Yawei
Abstract: Based on the survey data from the China National SME Survey Database in 2019, we analyze the relationship between executive financial literacy and the performance of Chinese small and medium‐sized enterprises (SMEs). We find that executive financial literacy helps improve corporate performance, especially for companies with weak external supervision and low competitive pressure. After controlling for the effects of the variables at the individual executive and enterprise levels, addressing possible endogenous problems in the analysis, robustness tests and heterogeneity analyses indicates that our findings remain unchanged. We further show that executive financial literacy improves corporate performance by alleviating corporate financing constraints and improving corporate risk management. Our findings have important policy implications for stimulating the vitality of economy and promoting high‐quality economic development.